Directional Photomanipulation of Breath Figure Arrays1. Issue 45 (22nd September 2014) - Wang, Wei; Du, Can; Wang, Xiaofan; He, Xiaohua; Lin, Jiaping; Li, Lei; Lin, Shaoliang
Abstract Porous polymeric films are of paramount importance in many areas of modern science and technology. However, processing methods typically based on direct writing, imprint, and lithography techniques have low throughput and are often limited to specific fabricated shapes. Herein, we demonstrate the directional photomanipulation of breath figure arrays (BFAs) formed by an azobenzene‐containing block copolymer to address the aforementioned problems. Under the irradiation of linearly polarized light, the round pores in the BFAs were converted to rectangular, rhombic, and parallelogram‐shaped pores in 30 min, due to the anisotropic mass migration based on the photo‐reconfiguration of the azobenzene units. Through a secondary irradiation after rotating the sample by 90°, the transformed pores were apparently recovered. Therefore, this non‐contacted, directional photomanipulation technique in conjunction with breath figure processing opens a new route to nano/microporous films with finely tuned features.